Socio-Demographic and Clinicopathological Features of Gastric Cancer: A Study of 114 Cases - Sarker, Mohammed Abu Kawsar; Rahman, Md Mizanur; Islam, Md Johirul; Nuruzzaman, AKM; Sultana, Mizhar (Journal of Chittagong Medical College Teachers' Association, 2016)
Gastric Cancer (GC) is one of the important malignancies which causes huge morbidity and mortality throughout the globe. This study was done to analyze the epidemiological and clinicopathological aspects of gastric cancer. It was a retrospective study conducted at National Institute of Cancer Research & Hospital, Dhaka from 1st January to 31st December 2013. In total, 114 histopathologically confirmed patients with GC were included in the study. Univariate methods (Mann-Whitney U-test, and Chisquare) were used for analysis. Among 114 cases, 81 (71.1%) were male. Sex ratio (Male: Female) was 2.45:1. The mean age of the patients was 52.9 years (SD ±12.6) at the time of the diagnosis. Weight loss, as a frequent symptom at the time of diagnosis, was observed in 85.1% of the cases. All of the patients were diagnosed with advanced pathologic stage and tumour grading was welldifferentiated 13.1%, moderate 51.8% and poorly differentiated 35.1%. In 72.8% of the patients, the tumours were located in the distal part of the stomach. All the patients were in the advanced stages of GC, which favours a poor survival. Male are more frequently affected female. lack of education, poor sanitation, high salt intake, low socioeconomic conditions are associated with increase chance of gastric cancer. Therefore, further comprehensive study of etiology and risk factors of GC, earlier detection in younger ages and in primary stages of tumour are needed. Weight loss, anorxia, abdominal pain and vomiting in elderly could be considered as alarm symptoms for GC diagnosis. JCMCTA 2016 ; 27 (1) : 51 - 54